2019
DOI: 10.1159/000502435
|View full text |Cite
|
Sign up to set email alerts
|

Can Less Intensive Chemotherapy and an Autotransplant Cure Adult T-Cell Acute Lymphoblastic Leukemia?

Abstract: T-cell acute lymphoblastic leukemia (T-ALL) is a rare disease usually treated with intensive, high-dose consolidation chemotherapy followed by an allotransplant in a substantial number of patients. The data of the RALL-2009 study on 125 adult T-ALL patients suggest that similar total chemotherapy doses given less intensively over a longer interval without interruptions and with an auto- rather than an allotransplant produce outcomes like current more intensive protocols and an allotransplant: 9-year cumulative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 15 publications
0
1
0
5
Order By: Relevance
“…In our study, we found that transplantation was still the critical treatment modality and could significantly improve the prognosis both in the ETP and the non-ETP groups. As to the insufficient knowledge of adult T-ALL, further improvements like therapeutic approaches and risk stratification are still needed (22)(23)(24).…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we found that transplantation was still the critical treatment modality and could significantly improve the prognosis both in the ETP and the non-ETP groups. As to the insufficient knowledge of adult T-ALL, further improvements like therapeutic approaches and risk stratification are still needed (22)(23)(24).…”
Section: Discussionmentioning
confidence: 99%
“…Медиана количества со бранных гемопоэтических стволовых клеток крови составила 4,52 (3,05) × 10 6 / кг. После кондицио нирования в режиме CEAM и последующей трансфу зии гемопоэтических стволовых клеток крови медиана восстановления лейкоцитов (>1 × 10 9 / л) составила 11 (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21) дней, тромбоцитов (>100 × 10 9 / л) -12 (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22) дней, гемоглобина (>100 г / л) -20 Иммунофенотипический вариант (по классификации EWALL) [16], n (%):…”
Section: результатыunclassified
“…21 (19) Медиана количества лейкоцитов в дебюте (диапазон), × 10 9 / л Median leukocytes at the onset (range), × 10 9 / L 22,4 (1,32-833,34) Количество лейкоцитов в дебюте >100 × 10 9 / л, n (%) Leukocytes >100 × 10 9 / L at the onset, n (%) 25 ( 23 13) 45 ( 47) 50 ( 53) 2 ( 2) 4 ( 4) 18 (18) 53 ( 54) 27 ( 28)…”
Section: результатыunclassified
See 2 more Smart Citations